IMPLEMENTATION OF INDUSTRIALIZATION POLICIES IN UZBEKISTAN AT THE MODERN STAGE OF ECONOMIC REFORMS - Abdulazizovich, Abduvokhidov Akmal; Bakhtiyarovich, Toshboev Bekzod; Islam, Abdugapparov (International Journal of Psychosocial Rehabilitation, 2020)
At the present stage of economic reforms, raising the competitiveness of the national economy is becoming more relevant than ever before. One of the main conditions for improving the competitiveness of the national economy is the implementation of a deep and well-considered long-term industrial policy. Therefore, this article attempts to highlight the issues of the implementation of industrialization policies in our country.